68Ga-Citrate Positron Emission Tomography of Healthy Men: Whole-Body Biodistribution Kinetics and Radiation Dose Estimates - Suilamo Sami; Li Xiang-Guo; Lankinen Petteri; Oikonen Vesa; Tolvanen Tuula; Luoto Pauliina; Viitanen Riikka; Saraste Antti; Seppänen Marko; Pirilä Laura; Hohenthal Ulla; Roivainen Anne (United States, 2022)
68Ga-citrate has one of the simplest chemical structures of all 68Ga-radiopharmaceuticals, and its clinical use is justified by the proven medical applications using its isotope-labeled compound 67Ga-citrate. To support broader application of 68Ga-citrate in medical diagnosis, further research is needed to gain clinical data from healthy volunteers. In this work, we studied the biodistribution of 68Ga-citrate and subsequent radiation exposure from it in healthy males.
Methods: 68Ga-citrate was prepared with an acetone-based radiolabeling procedure compliant with Good Manufacturing Practices. Six healthy males (age 41 ± 12 years, mean ± SD) underwent sequential whole-body PET/CT scans after an injection of 204 ± 8 MBq of 68Ga-citrate. Serial arterialized venous blood samples were collected during PET imaging and the radioactivity concentration was measured with a gamma counter. Urinary voids were collected and measured. The Medical Internal Radiation Dose (MIRD) bladder-voiding model with a 3.5 hour voiding interval was used. A model using a 70 kg adult male and MIRD schema was used to estimate absorbed doses in target organs and effective doses. Calculations were performed using OLINDA/EXM 2.0 software.
Results: Radioactivity clearance from the blood was slow, and relatively high radioactivity concentrations were observed over the whole of the 3 hour measuring period. Although radioactivity excretion via urine was rather slow (biological half-time, 69 ± 24 hours), the highest decay-corrected concentrations in urinary bladder contents were measured at 90 and 180 minute time points. Moderate concentrations were also seen in kidneys, liver, and spleen. The source organs showing the largest residence times were muscle, liver, lung, and heart contents. The heart wall received the highest absorbed dose of 0.077 ± 0.008 mSv/MBq. The mean effective dose (ICRP 103) was 0.021 ± 0.001 mSv/MBq.
Conclusion: PET imaging with 68Ga-citrate is associated with modest radiation exposure. A 200 MBq injection of 68Ga-citrate results in an effective radiation dose of 4.2 mSv, which is in the same range as other 68Ga-labeled tracers. This suggests the feasibility of clinical studies using 68Ga-citrate imaging in humans and the possibility of performing multiple scans in the same subjects across the course of a year.